A new world of health (United States of America. McGraw-Hill, Inc., 1977)
"The goal of this text is to provide a contemporary look at today's important health problems and to offer possible means of dealing effectively with them. I have chosen the "ecological approach" to the subject of health because people's total state of health is either directly or indirectly related to their interaction with the environment. For example, a person does not become spontaneously mentally ill; such illness is a reaction to certain factors that are present in the physical, social, or emotional environment. Other more obvious examples are the effects of the stresses of society on the use of drugs and alcohol. Further, in pushing for progress and affluence people have removed themselves from the physical activity necessary for maintaining a healthy existence, leading to skyrocketing increase in heart disease and circulatory disorders."
Includes index.
English text.
Keywords: Health